Predicting Individual Wellbeing Through Test Scores : Evidence from a National Assessment in Mexico - de Hoyos, Rafael; Estrada, Ricardo; Vargas, Maria Jose (World Bank, Washington, DC, 2018)
This paper constructs two longitudinal datasets that record students' test scores in a national standardized exam in Mexico and track students from the end of primary (Grade 6) to the end of lower (Grade 9) and upper (Grade 12) secondary school, then to university and labor market participation up to two years after graduation from upper secondary. The results show that test scores are a strong predictor of future education and labor market outcomes. Using a large sample of twins in the data, the paper shows that the relationship between Grade 6 test scores and future education outcomes goes beyond family background. Finally, the paper exploits the within-individual correlation between subject test scores and finds evidence that this standardized assessment captures in a meaningful way the specific skills that it is designed to measure. These results show that, despite their limitations, large-scale standardized tests can capture skills that are important for future individual wellbeing.